D-Shaped Left Ventricle, Anatomic, and Physiologic Implications - Eder Hans Cativo Calderon; Tuoyo O. Mene-Afejuku; Rachna Valvani; Diana P. Cativo; Devendra Tripathi; Hans A. Reyes; Savi Mushiyev (Case Reports in Cardiology)
Right ventricular loading/pressure influences left ventricular function because the two ventricles pump in series and because they are anatomically arranged in parallel, sharing the common ventricular septum. Flattening of the interventricular septum detected during echocardiographic examination is called D-shaped left ventricle. We present a case of an elderly male of African descent, who presented with increased shortness of breath. Transthoracic echocardiogram showed flattening and left sided deviation of interventricular septum causing a decreased size in left ventricle, secondary to volume/pressure overload in the right ventricle. While patient received hemodialysis therapy and intravascular volume was removed, patient blood pressure was noted to increase, paradox. Repeated transthoracic echocardiogram demonstrated less left deviation of interventricular septum compared with previous echocardiogram. We consider that it is important for all physicians to be aware of the anatomic and physiologic implication of D-shaped left ventricle and how right ventricle pressure/volume overload affects its function and anatomy.